Power Shunt Capacitor Bank Management Model Based on Life Expectancy and Risk Overtime (2022)
In this paper is presented a model to assess shunt power capacitor banks. The model seeks to support decision making by optimizing incomes and considering risk. Hence, to model incomes the revenue, maintenance cost, electrical losses, dismantling cost and risk are considered. The risk is monetized as a critical cost times probability of failure. Probability of failure is estimated using shunt bank degradation. To assess the model, the data of an operating shunt bank was used and the Colombian regulation was assumed for financial values. As a result, different maintenance strategies was evaluated in order to know the optimum one.